Body Politics in Beauty Pageants: A Study of Miss Nepal Discourse - Shrestha, Tara Lal (SCHOLARS: Journal of Arts & Humanities, 2023)
The paper attempts to explore how the female body is often controlled by the power politics, which is discussed with reference to the Miss Nepal beauty pageant. The pageant being organized since 1994 has drawn not only ideological and ethical debate, but it has also generated street demonstrations including violent confrontations since then. Though women’s wings of various politico-cultural organizations tried to stop it by organizing various protest movements, multiple forms of regional and community-based beauty pageants are proliferating in Nepal. This study primarily tries to observe the forms of body politics that exist in Miss Nepal beauty contests from the perspective of indigenous aesthetics. Secondly, it analyzes how the female body is tied with the power politics in the name of beauty pageants from the Gramscian notion of ‘hegemony’ and Ngugi wa Thiongo’s ‘decolonizing the mind’. Finally, as indigenous aesthetics is an extensive domain, this paper recommends some ways to deal with the Miss Nepal beauty pageant issues, especially with reference to the indigenous Newa: women aesthetics.